2022
DOI: 10.3389/fphar.2022.1048688
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal, phytochemical and pharmacological investigations of Baccharis dracunculifolia DC. (ASTERACEAE)

Abstract: Baccharis dracunculifolia DC (Lamiaceae) (Asteraceae) is found in South America, mainly in Argentina, Brazil, Bolivia, Paraguay and Uruguay. Folk medicine is used as a sedative, hypotensive, bronchodilator, cardiovascular disorders, anti-flu, and also in skin wounds. Considered the main source of green propolis, which increases the pharmacological interest in this species. It is also known as a “benefactor” plant facilitating the development of other plant species around it, being indicated for the recovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Also, Wang et al [88] identified apigenin and acacetin from P. cablin. Moreover, some reports showed the ovicidal, insecticidal, larvicidal, and acaricidal agents of polyphenols, e.g., p-coumaric, dihydrocoumaric, ferulic (E)-cinnamic, hydroxycinnamic, gallic, and caffeic acids [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Wang et al [88] identified apigenin and acacetin from P. cablin. Moreover, some reports showed the ovicidal, insecticidal, larvicidal, and acaricidal agents of polyphenols, e.g., p-coumaric, dihydrocoumaric, ferulic (E)-cinnamic, hydroxycinnamic, gallic, and caffeic acids [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Wormwood extract can be obtained using various extraction methods, including maceration, percolation, and Soxhlet extraction. The choice of extraction method can affect the composition and bioactivity of the extract [71].…”
Section: Wormwoodmentioning
confidence: 99%
“…Containing more than 500 recognized species, it is considered one of the largest genera within the family [18]. As previously reported by several phytochemical studies [19][20][21][22], the genus is known to afford a wide range of bioactive compounds, particularly terpenoids and flavonoids. Furthermore, some of these compounds have been found to display antitrypanosomal activity, such as those obtained from B. sphenophylla [23,24].…”
Section: Introductionmentioning
confidence: 97%